Sago Starch Bagea Cookies with Moringa Leaf Powder Composite as a Fiber and Antioxidant Enhancer - Herlina Herlina; Rodame Bonalisa Sinaga (Food ScienTech Journal, 2022)
Bagea is a traditional food typical of Eastern Indonesia such as the Ternate and Maluku regions. The addition of moringa leaf powder to bagea cookies can increase the nutritional content, so that it can meet the needs of dietary fiber and the antioxidant properties of bagea cookies. This study aims to determine the effect of adding moringa leaf powder to the physical, chemical and sensory characteristics of bagea cookies and to determine the best formulation of bagea cookies with sago starch with the addition of moringa leaf powder. This study used an experimental method with a completely randomized design (CRD) with a single factor, namely the addition of moringa leaf powder 3%, 6%, 9%, 12%, 15%. The tests included physical characteristics (color lightness, texture), chemical characteristics (moisture content, crude fiber content and antioxidant activity), sensory tests (color, aroma, texture, taste and overall) and effectiveness tests. The results showed that the addition of moringa leaf powder to bagea sago starch cookies had a significant effect on physical, chemical, sensory characteristics and gave no significant effect on the moisture content of bagea cookies. The best formulation of bagea cookies was in the L3 treatment which resulted in a color lightness characteristic of 76.42; texture; 262.92 g/2mm; moisture content 4.82%; crude fiber content 1.71%; antioxidant activity 8.52%; color preference 5.97 (slightly like-like); aroma preference 4.90 (neutral-slightly like); texture preference 5.33 (slightly like-like); taste preference 4.83 (neutral-slightly like); and overall preference of 5.57 (slightly like-like). The nutritional content of bagea cookies per 100 g is protein, fat, ash, and carbohydrates of 9.32%, 9.40%, 0,13%, and 76.30% respectively.